2021
DOI: 10.1360/ssc-2021-0122
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-doped gold nanoclusters with ultrasmall size andmicroenvironment-responsive visualized theranostics of tumor

Abstract: Inorganic nanoprobes with ultrasmall size have the advantage of kidney clearance, which was very meaningful for achieving clinical application. In this paper, Mn 2+ -doped gold nanoclusters (Mn-AuNCs) with ultrasmall size were synthesized, by which magnetic resonance imaging (MRI) and tumor-microenvironmentresponsive chemodynamic therapy (CDT) and photodynamic therapy (PDT) were achieved. The results showed that Mn-AuNCs nanoprobe occupied ultrasmall size of about 2-3 nm, and excellent T1-weighted MRI performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… 29 Previous studies have shown that Mn 2+ in doped materials mainly oxidizes to Mn 4+ . 11 , 46 , 47 Therefore, the XPS data of Mn 2p were carefully peak fitted and are presented in the inset of Figure 7 . The results show that Mn 2+ and Mn 4+ exist simultaneously, and the proportions of Mn 2+ and Mn 4+ are 42.77% and 57.23%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 Previous studies have shown that Mn 2+ in doped materials mainly oxidizes to Mn 4+ . 11 , 46 , 47 Therefore, the XPS data of Mn 2p were carefully peak fitted and are presented in the inset of Figure 7 . The results show that Mn 2+ and Mn 4+ exist simultaneously, and the proportions of Mn 2+ and Mn 4+ are 42.77% and 57.23%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The nHAPMn10 sample exhibited the highest magnetization value (0.34 emu/g), and the magnetization level of nHAP increased with increasing Mn doping concentrations, which is consistent with previous reports. 47 , 48 In addition, nHAPMn5 prepared at pH=12 showed relatively weak magnetization compared to that prepared at pH=10; however, the underlying mechanism is still unclear ( Figure S6 ).
Figure 9 Magnetization curves of nHAP and nHAPMn powders measured at room temperature.
…”
Section: Resultsmentioning
confidence: 99%